2015
DOI: 10.1073/pnas.1411514112
|View full text |Cite
|
Sign up to set email alerts
|

In-cell SHAPE reveals that free 30S ribosome subunits are in the inactive state

Abstract: It was shown decades ago that purified 30S ribosome subunits readily interconvert between "active" and "inactive" conformations in a switch that involves changes in the functionally important neck and decoding regions. However, the physiological significance of this conformational change had remained unknown. In exponentially growing Escherichia coli cells, RNA SHAPE probing revealed that 16S rRNA largely adopts the inactive conformation in stably assembled, mature 30S subunits and the active conformation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 25 publications
6
72
0
1
Order By: Relevance
“…However, recent reports have suggested that 1M7, an isatoic anhydride reagent related to NMIA, was able to robustly modify both ribosomal RNA as well as mRNAs inside both mammalian and bacterial cells (McGinnis et al 2015;Smola et al 2015;Takahashi et al 2016;Watters et al 2016). These apparently contradictory results stimulated us to further investigate the differences between the two types of SHAPE reagents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent reports have suggested that 1M7, an isatoic anhydride reagent related to NMIA, was able to robustly modify both ribosomal RNA as well as mRNAs inside both mammalian and bacterial cells (McGinnis et al 2015;Smola et al 2015;Takahashi et al 2016;Watters et al 2016). These apparently contradictory results stimulated us to further investigate the differences between the two types of SHAPE reagents.…”
Section: Resultsmentioning
confidence: 99%
“…Published work has reported in vivo modification of RNA in E. coli cells; however, no cDNA truncation blots were shown (McGinnis et al 2015;Smola et al 2015;Takahashi et al 2016). To address the possibility that our lack of in vivo signal using 1M7 is due to the type of cells used, we repeated the SHAPE experiment in HST08 E. coli cells following precisely the published protocols for cell culture, RNA modification, and RNA extraction (McGinnis et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The large 70S peak of these gradients includes translating monosomes as well as ribosomes that finish translation before cell lysis (8)(9)(10). Bearing this in mind, we infer that SSU particles lacking S3, S10, S14, and S21 accumulate in the ΔlepA mutant but do not efficiently enter the actively translating pool of ribosomes.…”
Section: Significancementioning
confidence: 87%
“…Taking this notion a step further, if we generated improved models of the data and concurrently integrated them into model-based decoding schemes such as RNAprob, then this has the potential to lead to better predictions. Recently, McGinnis et al (2015) showed that free 30S ribosome subunits are in the inactive state. In particular, the functionally important h28-h44 region contains an alternative structure inconsistent with the conventional reference.…”
Section: Datamentioning
confidence: 99%